2016
DOI: 10.1111/adb.12416
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory signaling regulates voluntary alcohol intake and stress-induced consumption after exposure to social defeat stress in mice

Abstract: Proinflammatory activity has been postulated to play a role in addictive processes and stress responses, but the underlying mechanisms remain largely unknown. Here, we examined the role of interleukin 1 (IL-1) and tumor necrosis factor-α (TNF-α) in regulation of voluntary alcohol consumption, alcohol reward and stress-induced drinking. Mice with a deletion of the IL-1 receptor I gene (IL-1RI KO) exhibited modestly decreased alcohol consumption. However, IL-1RI deletion affected neither the rewarding properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Interestingly, this is consistent with studies finding innate immune signaling contributes to the development of AUD (Crews et al., 2017; de Timary et al., 2017). Innate immune signaling cytokines alter EtOH consumption (Marshall et al., 2017, 2017), and cytokine receptors contribute to stress‐induced EtOH consumption (Karlsson et al., 2017). Further, immune signaling molecules are increased in postmortem human alcoholic brain (Crews et al., 2017) and regulate preference for alcohol drinking in animal studies (Mayfield et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this is consistent with studies finding innate immune signaling contributes to the development of AUD (Crews et al., 2017; de Timary et al., 2017). Innate immune signaling cytokines alter EtOH consumption (Marshall et al., 2017, 2017), and cytokine receptors contribute to stress‐induced EtOH consumption (Karlsson et al., 2017). Further, immune signaling molecules are increased in postmortem human alcoholic brain (Crews et al., 2017) and regulate preference for alcohol drinking in animal studies (Mayfield et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, reducing endotoxin release with antibiotics, probiotics, and drugs resulted in a loss of the stress hormone response, suggesting stress‐induced changes in blood endotoxin contribute to stress hormone responses (Ait‐Belgnaoui et al., 2012). Innate immune signaling cytokines also alter EtOH consumption (Marshall et al., 2016, 2017), and the cytokine receptors IL1R1 and TNFR1 contribute to stress‐induced EtOH consumption (Karlsson et al., 2017), suggesting the neuroimmune system may contribute to addiction. Cytokines also enhance stressful emotional states following alcohol withdrawal (Breese et al., 2008).…”
mentioning
confidence: 99%
“…In preclinical models of male social defeat stress, B6 or Swiss-derived outbred male mice exposed to repeated attacks from a dominant male resident later consume significantly more alcohol than non-defeated controls ( Fig. 1 ; Albrechet-Souza et al, 2017 ; Hwa et al, 2016a ; Karlsson et al, 2017 ; Kudryavtseva et al, 2006 ; Kudryavtseva et al, 1991 ; Nelson et al, 2018 ; Newman et al, 2018 ; Norman et al, 2015 ). Recently, we developed a model of social stress that promotes inter-female aggression to evaluate the effects of social defeat stress on alcohol consumption in female B6 mice (Newman et al in prep).…”
Section: Animal Models Of Social Stress and Pathological Patterns Of mentioning
confidence: 99%
“…In addition to the classical proinflammatory and potentially neurotoxic activation phenotype, microglia are now recognized to exhibit several alternative phenotypes related to motility, phagocytosis, repair, and anti-inflammatory responses, which are associated with the formation and proper function of neuronal circuits (Frost and Schafer, 2016;Sousa et al, 2017) with microglia-derived neurotrophic factors playing a key role (Parkhurst et al, 2013). The involvement of neuroimmune responses has been implicated in the pathophysiology of alcohol use disorders (Blednov et al, 2012;Karlsson et al, 2017). Various in vitro and animal studies have reported a spectrum of microglial phenotypes in responses to EtOH, ranging from classical proinflammatory (Pascual et al, 2011;Qin and Crews, 2012a;Qin and Crews, 2012b) to noninflammatory phenotypes (Bell-Temin et al, 2015;Bell-Temin et al, 2013;Guergues et al, 2020;Marshall et al, 2013) and a mix of both (Peng et al, 2017).…”
mentioning
confidence: 99%